1995
DOI: 10.1103/physreva.52.2136
|View full text |Cite
|
Sign up to set email alerts
|

Absolute cross sections for charge capture from Rydberg targets by slow highly charged ions

Abstract: A crossed beam experiment has been used to measure absolute charge capture cross sections in collisions of slow highly charged xenon ions with laser excited Rydberg atoms. The cross sections were measured for scaled projectile velocities nv" from 1.0 to 6.0, for projectile charges of 8, 16, 32, and 40, where n is the principal quantum number of the target electron. Experimental cross sections are compared with predictions of classical models.PACS number(s): 34.60.+z, 34.70.+e A substantial amount of work has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Therefore, the capture when laser 3 is off must be from the ground state, 5s, or intermediate states 5p or 4d. Also, capture from the intermediate states was found to be less than 0.2% [3]. This allows the derivation of the capture probability to be simplified into a two-state (ground state and Rydberg state) system: I on,off 0 : the incoming projectile flux with lasers on or off, respectively; I (x): the projectile flux at position x inside the target; σ g,r : single-capture cross section from ground-or Rydberg-state rubidium, respectively; ρ g,r : density distribution for ground-or Rydberg-state rubidium, respectively; S on,off : the total number of single-capture events with laser on or off, respectively; l g,r : target length for ground-or Rydberg-state rubidium, respectively.…”
Section: Capture Probabilitymentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, the capture when laser 3 is off must be from the ground state, 5s, or intermediate states 5p or 4d. Also, capture from the intermediate states was found to be less than 0.2% [3]. This allows the derivation of the capture probability to be simplified into a two-state (ground state and Rydberg state) system: I on,off 0 : the incoming projectile flux with lasers on or off, respectively; I (x): the projectile flux at position x inside the target; σ g,r : single-capture cross section from ground-or Rydberg-state rubidium, respectively; ρ g,r : density distribution for ground-or Rydberg-state rubidium, respectively; S on,off : the total number of single-capture events with laser on or off, respectively; l g,r : target length for ground-or Rydberg-state rubidium, respectively.…”
Section: Capture Probabilitymentioning
confidence: 93%
“…(Ambient light levels cause a positive bias on the detector output so that the peak on the lower end of the spectrum is offset from 0.) Previous studies [3,11] showed that above a rather low threshold, the number of Rydberg atoms should be a linear function of the intensity of the blue fluorescence. In order to obtain consistently normalized cross sections, the data were re-sorted using blue intensity plots like that in figure 5.…”
Section: Relative Cross Sectionsmentioning
confidence: 93%
See 2 more Smart Citations
“…This will be placed orthogonal to the ion path to allow the injection of the rubidium beam into the center of the re-capture Penning trap. A two- [70] or three-laser excitation scheme [71] can be used to excite the rubidium atoms to a Rydberg state. These Rydberg rubidium atoms will be injected into the Penning trap, where they will undergo resonant charge exchange [72] with trapped, fully-ionized helium and neon ions to form one-electron ions in Rydberg states.…”
mentioning
confidence: 99%